60 GHz antenna module featuring spherical coverage for nomadic and mobile Gbps applications - Hong, Wonbin; Baek, Kwang-Hyun; Kim, Yoon Geon (2015 USNC-URSI Radio Science Meeting (Joint with AP-S Symposium), 2015)
Employing efficient, high directivity antennas is one of the most preferred techniques to alleviate the high material and atmospheric propagation loss which are commonly associated at millimeter-wave (mmWave) spectrum. Over the past decade, significant strides have been made in proliferating mmWave wireless technologies across a diverse range of user applications and markets. Consequently in addition to relatively well understood user scenarios such as mmWave backhaul and fixed point-to-point communication, the wireless industry has been actively investigating nomadic and mobile mmWave scenarios with focus on consumer electronics. For example, compact 60 GHz portable modules can be conceived in the form that resemble conventional USB dongles to support multi-Gbps wireless links for portable wireless devices. Mobile mmWave devises will most certainly be subject to frequent channel variations particularly due to constant orientation and position shifts. Extensive adaptive beamforming methodologies have been devised and researched by numerous research entities to ensure a secure wireless quality of service (QoS). However the effectiveness of mmWave adaptive beamforming algorithms are oftentimes diminished in non-line-of-sight (NLOS) propagation conditions which can eventually lead to wireless link failures. One of the primary factors that attribute to this practical but important technical challenge is the limited beam steering range associated with planar mmWave antennas such as broadside arrays. Ensuring high antenna gain across a wide range of atmosphere is subject to a series of technical tradeoffs and remains of the most elusive subjects in the mmWave wireless industry.